The Value of Ibn al-‘Atiyyah’s Qur’ânic Interpretation in the Light of Method of Quotation with Poem (Istishhâd) - Öğmüş, Harun (Sakarya University, 2009)
The work on Qur’ânic interpretation called al-Muharrar al-Wajîz fî Tafsîr al-Kitâb al-‘Azîz by Abû Muhammad Abd al-Haqq Ibn Ghâlib Ibn al-Atiyyah al-Ghirnâtî (d. 541/1146), is usually compared with Jar Allah al-Zamahsharî’s al-Kashshaf. Although al-Muharrar is mainly concerned with narrative interpretation, it is one of works which frequently cites poem as evidence (istishhâd). In this article, we shall explore the passages where poems have been quoted as an evidence of a particular meaning for particular word(s) in this work. Besides, it is found out that the most significant source of Ibn al-Atiyyah when he is quoting the poems is Tabârî’s Tafsîr. It is also concluded that Ibn Atiyyathe author of al-Muharrar sometimes makes importants observations and significant analyses about shawâhid, i.e. the poems quoted as way of evidence.

The work on Qur'anic interpretation called al-Muharrar al-Wajîz fî Tafsîr al-Kitab al-'Azîz byAbû Muhammad Abd al-Haqq Ibn Ghalib Ibn al-Atiyyah al-Ghirnatî (d. 541/1146), is usuallycompared with Jar Allah al-Zamahsharî's al-Kashshaf. Although al-Muharrar is mainlyconcerned with narrative interpretation, it is one of works which frequently cites poem asevidence (istishhad). In this article, we shall explore the passages where poems have beenquoted as an evidence of a particular meaning for particular word(s) in this work. Besides, it isfound out that the most significant source of Ibn al-Atiyyah when he is quoting the poems isTabarî's Tafsîr. It is also concluded that Ibn Atiyyathe author of al-Muharrar sometimes makesimportants observations and significant analyses about shawahid, i.e. the poems quoted asway of evidence.
İBN ATIYYE’NİN TEFSÎRİNİN ŞİİRLE İSTİŞHAD YÖNTEMİ AÇISINDAN DEĞERİ